STRATEGI BERTAHAN HIDUP PETANI PENGGARAP PASCA PENGGUSURAN (Studi Pada Lokasi Pembangunan Kota Baru Lampung, Kecamatan Jati Agung, Kabupaten Lampung Selatan) - Ersan, Mares; Ikram, Ikram (SOCIOLOGIE, 2013)
Type of research used in this research is descriptive qualitative in-depth interviews. Based on the research and discussion by the author, the strategy undertaken by the tenants after the eviction Who was affluent, has a steady job working the land, they will have to suffer a very difficult psychological pressure was also how they feel. Survival strategies heâs do very diverse, from catfish cultivation, labor, selling pecel even to sell the items they have. Most of all informants who work the land Eks-LIPI lost their jobs. It can be concluded reasons sharecroppers Land Eks-LIPI InJatiAgungto switch jobs after the eviction. Economic insistence, to provide for the family, do not have more arable land, less income and do not have a job. In addition, how to work the land sharecroppers Eks-LIPI In JatiAgungafter the eviction carried out by rate commute every day, come home once a week, came home a few weeks, once a month and returned home a few months. As most of the location/work many peasants away or are outside the district/area. The government is expected prior to implementing development programs should be thoroughly reviewing the program carefully so as not to cause adverse effects on society. So also with the community, it should not be too quick to be arrogant that emphasizes emotional moment that could trigger riots, lets think wise, act wisely, increase levels of intellect, in this way is expected to create a harmonious relationship, harmony, secure, peaceful and dignified . Conflicts between people with the government that exists between the existing tenants JatiAgung, Lampung Selatan is one example of conflict caused by arable land confiscation by the government will conduct the Kota Barudevelopment projects Lampung. Which compensation or rope asihnya not comply with community expectations. Hopefully in the future, social conflicts of this kind are no longer appearing in life because it will be detrimental to all parties. The government should really can protect the public and the public must adhere to the government so that harmony can be created.Keywords: Strategy, survival, sharecroppers, post eviction